UNDERSTANDING FLASH FICTION BY THE SIX-WORD STORY: “FOR SALE: BABY SHOES, NEVER WORN” - Frederik Agnar Widjaja (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2020)
Literary work never limits itself to any type or idea. Discussing fiction, sometimes we do not mention flash fiction: a type of very short story, even only a few words, but can contain so many interpretations according to each reader. This study shows the history, elements, and characteristics of flash fiction as a type of prose. For Sale: Baby Shoes, Never Worn is one of the well-known flash fiction stories. Although generally attributed to Ernest Hemingway, the link to him is unsubstantiated. We can analyze this six-word story into every two words of each sentence: the meaning of “For Sale”, “Baby Shoes”, and “Never Worn”. In this way, we can have many interpretations for each word and also the meaning as a whole.